(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2009)
Influence of landslides of Armenia on transport communications and populated areas is examined; examples and sizes of areas in separate regions of the republic liable to landslide and districts, which are in the most critical situation, are selected. The conclusion that large damage of the territory of Armenia is the result of incorrect economic activity of the man on the whole and absence of preventive anti-landslide measures is drawn. The necessity of forming a joint scientific centre for research of landslides is marked.